Outdoor And Folk Games In The System Of Physical Education Of Schoolchildren - (PhD),Dos.S.A. Akhmedova; Dos. S.N. Haydarov; Teacher N.O.Pirimova (Genius Publishing Group, 2024)
This article examines outdoor and folk games in the system of physical education of schoolchildren; the qualitative originality of games is determined by their goals, content, playing conditions and means, and characteristics of the participants.
Keywords: Sports; physical education; outdoor games